Relevance of Interventionist Pedagogical Approaches in the Context of Nepal (Tribhuvan Journal, 2025)
This paper examines the context of using traditional pedagogical approaches and the need of intervention to these traditional pedagogical approaches in the context of Nepal. Particularly, it aims to explore how the interventionist pedagogical approaches are relevant in the context of Nepal. I reviewed several books, journals and research articles to examine the shift in pedagogical approaches in global context, the emergence of interventionist pedagogies approaches and relevance of these approaches in the context of Nepal. From the review of various sources, I found the need of intervention to these existing traditional pedagogical approaches as they could not provide the equal opportunities as well as benefits of education to the diverse learners’ population. This study further explored the relevance of interventionist pedagogical approaches in the context of Nepal where the existing pedagogical approaches have excluded many students from getting benefits of education and only prioritized the narrative way of learning that focuses only on rote learning and memorization. I also found that the interventionist pedagogical approaches as a panacea to many existing problems related with teaching and learning process. This study suggests to intervene the existing traditional pedagogical approaches and follow interventionist pedagogical approaches to offer equal benefits of education to people from all walks of life in democratic environment.